2020
DOI: 10.1097/md.0000000000023138
|View full text |Cite
|
Sign up to set email alerts
|

Image quality improvement of single-shot turbo spin-echo magnetic resonance imaging of female pelvis using a convolutional neural network

Abstract: We have developed a deep learning-based approach to improve image quality of single-shot turbo spin-echo (SSTSE) images of female pelvis. We aimed to compare the deep learning-based single-shot turbo spin-echo (DL-SSTSE) images of female pelvis with turbo spin-echo (TSE) and conventional SSTSE images in terms of image quality. One hundred five and 21 subjects were used as training and test sets, respectively. We performed 6-fold cross validation. In the training process, low-quality images were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Our study showed that, for overall image quality, radiologists preferred DL-reconstructed images over non–DL-reconstructed images ( P < 0.0001). Recently published literature has shown improvements in the image quality in the female pelvis with DL reconstruction 7,8 . To our knowledge, this is the first study to assess the DL reconstruction method for the PROPELLER sequence in patients with gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our study showed that, for overall image quality, radiologists preferred DL-reconstructed images over non–DL-reconstructed images ( P < 0.0001). Recently published literature has shown improvements in the image quality in the female pelvis with DL reconstruction 7,8 . To our knowledge, this is the first study to assess the DL reconstruction method for the PROPELLER sequence in patients with gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 92%
“…Recently published literature has shown improvements in the image quality in the female pelvis with DL reconstruction. 7,8 To our knowledge, this is the first study to assess the DL reconstruction method for the PROPELLER sequence in patients with gynecologic malignancies. A recently published study using DL reconstruction in prostate MRI also showed improved image quality in T2-weighted FSE.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the deep learning protocol showed improved image quality compared with the NAÏVE one. To the best of our knowledge, there are no studies performed on abdominal DWI; however, Misaka et al [ 17 ] conducted an interesting study on female pelvis. They built a deep learning algorithm to improve single-shot turbo spin-echo (SSTSE) sequences and compare them with TSE, considered as ground truth, and SSTSE.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent development of deep-learning, superresolution (SR) technology as an image postprocessing technology can be implemented in clinical practice (13)(14)(15). In particular, generative adversarial networks (GANs) (16) are deep neural network architectures in which two networks are configured to face each other and have attracted much attention in processing natural images and medical images (17,18).…”
Section: Introductionmentioning
confidence: 99%